Interest groups and economic performance: Some new evidence - Klaus W. Zimmermann; Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2008)
Mancur Olson's theory of the decline of nations is path-breaking in political economics. It has been tested cross-sectionally in numerous empirical studies. We survey the existing results briefly, with a special focus on studies using the number of lobbies as an exogenous variable. Using data from the period 1973-2006, we then present the field's first time-series analysis of the effects of the number of interest groups on the German lobby list and macroeconomic performance, gauged in terms of economic growth and inflation. The number of interest groups (as a proxy for their influence) is shown to have an important impact on macrovariables: Interest group activity significantly leads to a decline in the growth rate and a rise in the inflation rate.
urn:nbn:de:gbv:705-opus-17183
Keywords: D61; 330; Interest groups; economic performance; growth rate; inflation rate; Interessenvertretung; Interessenpolitik; Public Choice; Wirkungsanalyse; Wirtschaftswachstum; Inflationsrate; Deutschland